Risk Factors Associated with the Incidence of Hypertension in the Work Area of Soe City Health Center - Uy, Giovani Kristin; Purnawan, Sigit; Landi, Soleman (Timorese Journal of Public Health, 2024)
Hypertension or high blood pressure is a common chronic disease worldwide and a major risk factor for cardiovascular disease. Data from the World Health Organization (WHO) 2019 shows that the global prevalence of hypertension is 22% of the total world population. The 2018 Riskesdas showed that in Indonesia the prevalence of people with high blood pressure reached 34.1% higher than the prevalence in 2013 of 25.8%. The purpose of this study was to analyze the risk factors associated with the incidence of hypertension in the working area of ​​the Community Health Center in Soe City, South Central Timor District. The method used in this research is an analytic survey with a case control research design. There were 124 samples in this study consisting of 62 cases and 62 controls. Sampling of this study using simple random sampling technique. Data analysis used the chi-square statistical test and calculated the strength of the risk factor relationship using the odds ratio (OR). The dependent variable in this study was hypertension while the independent variables were age, gender, smoking habits, physical activity, obesity and salt consumption. The results showed that the variables that had a relationship with the incidence of hypertension were age (p=0.000, OR=35,974), gender (p=0.035, OR=0.404), smoking habits (p=0.017, OR=2.928), physical activity (p=0.002, OR=3.657), obesity (p=0.000, OR=4.191) while salt consumption has no relationship with the incidence of hypertension. Suggestions for the community to further improve healthy lifestyles such as reducing smoking habits, doing regular physical activity, and always maintaining a diet and carrying out routine blood pressure checks to health services.